Distribution of Zinc in Mycelial Cells and Antioxidant and Anti-Inflammatory Activities of Mycelia Zinc Polysaccharides from Thelephora ganbajun TG-01. (17th June 2020) - Zheng, Lan; Ma, Yaohong; Zhang, Yunjuan; Meng, Qingjun; Yang, Junhui; Gong, Weili; Liu, Qingai; Cai, Lei; Hao, Lujiang; Wang, Binglian; Yang, Yan
Abstract : This study demonstrates that Thelephora ganbajun had a strong ability to absorb zinc, and zinc can be compartmentally stored in the small vesicles and mainly accumulated in the form of zinc-enriched polysaccharides (zinc content was 25.0 ± 1.27   mg / g ). Mycelia zinc polysaccharides (MZPS) and its fractions were isolated. The main fraction (MZPS-2) with the highest antioxidant activity in vitro was composed of mannose : galacturonic acid : glucose : galactose in a molar ratio of 61.19 : 1 : 39.67 : 48.67, with a weight-averaged molecular weight of 5.118 × 10 5   Da . MZPS-2 had both α -pyranose and β -pyranose configuration and had a triple helical conformation. By establishing zebrafish models, we found that MZPS-2 can significantly scavenge free radicals, reduce the generation of reactive oxygen species caused by inflammation, and inhibit the recruitment of neutrophils toward the injury site. Therefore, MZPS-2 exhibited antioxidant and anti-inflammatory effects and can be used as a zinc supplement with specific biological activities to alleviate zinc deficiency complications, such as chronic oxidative stress or inflammation.